Comparison of the photoelectric and the intersection methods of estimating root area, root lengh and mean root radius - Rossiello, Roberto Oscar Pereyra; Araújo, Adelson Paulo; Manzatto, Celso Vainer; Fernandes, Manlio Silvestre (Pesquisa Agropecuaria Brasileira, 1995)
The study of root system requires quantitative methods that combine speed and precision. The intersection method, that estimates the length through counting intersections between root segments and a gridline, and the photoelectric method, that measures the area with an electronic area meter, were compared on estimating root length, root surface area, and mean root radius. The methods were gauged against plastic wires with diameters of 0.7, 1.19 and 3.55 mm, showing similar precision and accuracy. For maize (Zea mays L.) plants grown in soil and in nutrient solution, the intersection method underestimated the values of area and length on fine roots (diameter < 2 mm). The discrepancy between methods was higher in nutrient solution grown plants. The same operator spent an average of 4.0 and 15.6 min. per 10 m of roots, on the execution of the photoelectric and the intersection methods, respectively. Using sub-samples with 20% of total roots volume, the photoelectric method produced satisfactory results, but the intersection method generated high values of coefficient of variation. The uses of the photoelectric method on quantification of root parameters and influx of nutrients area discussed.